Comparative studies on fermentation products of cocoa beans - Abd. Samah, Othman; Ibrahim, N.; Alimon, H.; Karim, M. I. Abdul (1993)
The maximum amounts of acetic acid produced by ripe and unripe cocoa beans were 157 mg and 110 mg/10 g wet wt of cotyledon, respectively. The unripe beans had a lower pH than the ripe beans after 6 days' fermentation. About 40% of ripe beans achieved a chocolate colour compared with 27% of unripe beans.